2005
DOI: 10.1128/aem.71.2.741-745.2005
|View full text |Cite
|
Sign up to set email alerts
|

Active Transport and Accumulation of Iodide by Newly Isolated Marine Bacteria

Abstract: Iodide (I؊ )-accumulating bacteria were isolated from marine sediment by an autoradiographic method with radioactive 125 I ؊ . When they were grown in a liquid medium containing 0.1 M iodide, 79 to 89% of the iodide was removed from the medium, and a corresponding amount of iodide was detected in the cells. Phylogenetic analysis based on 16S rRNA gene sequences indicated that iodide-accumulating bacteria were closely related to Flexibacter aggregans NBRC15975 and Arenibacter troitsensis, members of the family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 37 publications
0
36
0
1
Order By: Relevance
“…After washing, cells were resuspended in the same buffer to achieve optical density at 600 nm of 1.0 (equivalent to 0.5 mg (dry weight)] ml Ϫ1 ). The transport assay was carried out essentially as described previously (4). Briefly, the cell suspension was incubated aerobically with 0.1 M potassium iodide and 74 kBq ml Ϫ1 radioactive iodine tracer (Na 125 I; Amersham Bioscience).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After washing, cells were resuspended in the same buffer to achieve optical density at 600 nm of 1.0 (equivalent to 0.5 mg (dry weight)] ml Ϫ1 ). The transport assay was carried out essentially as described previously (4). Briefly, the cell suspension was incubated aerobically with 0.1 M potassium iodide and 74 kBq ml Ϫ1 radioactive iodine tracer (Na 125 I; Amersham Bioscience).…”
Section: Methodsmentioning
confidence: 99%
“…When C-21 was cultured in a liquid medium containing 0.1 M iodide, the strain removed 80% of iodide from the medium within 24 h and accumulated iodine in the cells with a maximum concentration factor of 5.5 ϫ 10 3 (4). The initial uptake rates of iodine by washed cells of C-21 showed substrate saturation kinetics with an apparent affinity constant for transport of 0.073 M. Interestingly, the cells took up iodine only in the presence of glucose (4). In this study, iodine transport by a washed cell suspension of C-21 was assayed for further understanding of the mechanism of iodine uptake by C-21.…”
mentioning
confidence: 99%
“…Finally, HIO is translocated freely across the cell membrane. Since the initial rate of uptake by C-21 showed substrate saturation kinetics 7) , HIO is probably transported via carrier-mediated facilitated diffusion. In the cells, HIO should be reduced to iodide again, or be associated with certain organic compounds, to avoid a release of iodine from the cells.…”
Section: Accumulation Of Iodinementioning
confidence: 99%
“…In 2005, an iodine-accumulating bacterium, designated strain C-21, was isolated from surface marine sediment 7) . This strain was phylogenetically closely related to a marine aerobic bacterium, Arenibacter troitsensis, a member of the family Flavobacteriaceae.…”
Section: Accumulation Of Iodinementioning
confidence: 99%
“…Bacteria can accumulate iodine, through either electrostatic adsorption on the cell surface or via electrophilic substitution of cellular organic molecules. Strains isolated from seawater and marine sediments can concentrate iodide by a factor of 6 × 10 3 , but efforts to identify iodine accumulating strains from soils or among anaerobic bacteria common in subsurface aquifers failed (Amachi et al, 2010;Amachi et al, 2005a). Iodide accumulation ability was tested among 136 bacterial strains isolated from sediments of an 129 I-contaminated, aerobic aquifer in F Area of the SRS and three strains were identified that accumulated low levels of iodide (0.2 to 2.0% of a 0.1 μM solution; 1 -2 orders of magnitude less than that of the marine strains that accumulate iodide) .…”
Section: Relevance Of Microbial Processes Influencing 129 I Behavior mentioning
confidence: 99%